Regional variations in need for and provision and use of child health services in England and Wales. Issue 6040 (9th October 1976) - West, R R; Lowe, C R
Abstract : An analysis of indicators of the need for and provision and use of child health services in the 15 pre- 1974 hospital board regions in England and Wales showed that need and provisions were badly matched. There was a high degree of correlation between the indices within each of the three groups, indicating that a region with a small provision in one area of child health services would tend to have few resources in other areas also. Statistics on the use of services relate more to the provision of those services than to the need for them. Regions with large resources will justify these resources by claiming that their use statistics indicate needs, whereas they really indicate met demands. It is more important to identify demands and needs that are not being met.